Synthesis and Characterization of Vanadium Substituted Potassium Tungsten Bronzes, KxVyW1-yO3 - Abdullah, A. M.; Debnath, T.; Rüscher, C. H.; Hussain, A. (Journal of Scientific Research, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE BN-BD <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:14.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Vrinda; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> A series of vanadium substituted potassium hexagonal tungsten bronzes KxVyW1-yO3 (K-HTB) were prepared by conventional solid state method at 800 °C with compositions of x = 0.30 and 0.00 ? y ? 0.15. A mixture of K-HTB and non bronze phases with y ? 0.20 was observed. The proportion of this non bronze phase increases with increasing vanadium content. The non bronze phases in the mixture could not be indexed yet. In contrast, a very small amount of vanadium can be substituted in potassium tetragonal tungsten bronzes (K-TTB) at 800 °C with x = 0.50 and 0.00 ? y ? 0.02, however at 700 °C vanadium substituted K-TTB can be prepared with 0.00 ? y ? 0.05. Further substitution of vanadium in K-TTB decomposes to K-HTB and non-bronze phases. Keywords: Tungsten bronzes; Vanadium substituted bronze; Bronzoids. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.9349 J. Sci. Res. 4 (2), 507-514 (2012)